Under pressure: an integrated assessment of human activities and their potential impact on the ecosystem components of the Southern Brazilian continental shelf - Marinez E. G. Scherer; Gabriela D. Sardinha; Vitor de Souza; Tiago B. R. Gandra; Sergio R. Floeter; Ana M. R. Liedke; Amanda R. Rodrigues; Jarbas Bonetti; Vicente Gomes; Lohengrin Fernandes; Débora S. Ferrari; Fernanda C. Silva; et al. (npj Ocean Sustainability, 2024)
Abstract Economic activities in the South Brazilian Shelf (SBS) are concentrated on the coast, causing several impacts. To balance biodiversity and habitat conservation in coastal and marine areas with human activities relevant to society, it is important to identify and understand those sectors and pressures. We conducted an analysis to assess ecosystem risks from multiple drivers and pressures in the continental shelf that extends from the Southernmost point of Brazil (Chuí) to Cabo Frio cape, in Rio de Janeiro State. We used the Integrated Ecosystem Assessment (IEA) methodology, a framework for implementing ecosystem-based management grounded on five steps: scoping, indicator development, ecosystem assessment, risk analysis, and management strategy evaluation. This work presents the scoping step consisting of a semi-quantitative assessment identifying sector–pressure–ecological component pressure pathways. Subsequently, these pathways were scored using expert judgment supported by literature and data, regarding their level of overlap with each ecosystem component, frequency of occurrence, and degree of impact, enabling estimation of the magnitude of impact risk arising from each one of the sectors and pressures. The assessment involved 20 experts from multiple disciplines and backgrounds. To validate the results, we conducted a thorough literature review and engaged in further discussions with relevant stakeholders. As a result, 16 sectors and 19 pressures were identified as impacting 18 ecological components. Fishing, land-based industry, tourism and recreation, wastewater, and coastal infrastructure represented the main economic sectors impacting the area. The major associated pressures were the incidental catch of species, the introduction of contaminants and organic matter into the water, and the generation of waste. The most affected ecosystem components were, in turn, those located on or close to the coast, such as mangroves, saltmarshes, and rocky reefs while the preeminent impacted taxonomic groups were elasmobranchs, seabirds, reptiles, mammals, and bony fish. The literature review supported the expert assessment, and the stakeholders’ workshop endorsed our findings. Additionally, this assessment highlights the need to implement public policies that focus on reducing the impact of the most influential sectors and pressures and the necessity of strengthening research and monitoring. Identifying these priorities for integrated coastal and marine management is crucial, and our research outcomes can be key in promoting regional ocean sustainability.